Infección del tracto urinario por Corynebacterium renale en un cuy hembra mascota (Cavia porcellus) – Reporte de caso - Palomino-Farfán, Joel André (2025)
A 10-month-old black mixed-breed female pet guinea pig was evaluated for polydipsia, pollakiuria, and haematuria. A clinical evaluation including a physical examination and complementary tests such as abdominal ultrasound, urinalysis, and urine culture confirmed a urinary tract infection (UTI) caused by Corynebacterium renale. The bacteria were identified by conventional culture, colony morphology, and biochemical tests, and subsequently confirmed through 16S rRNA gene amplification and sequencing. Enrofloxacin, meloxicam, and a dietary change were the treatment options for resolution.